2012
DOI: 10.1002/nme.3349
|View full text |Cite
|
Sign up to set email alerts
|

A meshfree‐enriched finite element method for compressible and near‐incompressible elasticity

Abstract: SUMMARY In this paper, a two‐dimensional displacement‐based meshfree‐enriched FEM (ME‐FEM) is presented for the linear analysis of compressible and near‐incompressible planar elasticity. The ME‐FEM element is established by injecting a first‐order convex meshfree approximation into a low‐order finite element with an additional node. The convex meshfree approximation is constructed using the generalized meshfree approximation method and it possesses the Kronecker‐delta property on the element boundaries. The gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…Because the isoparametric mapping defined in Equation (2) reproduces constant and bilinear fields, it can be shown that the proposed element‐wise nodal integration scheme theoretically preserves the element area . As a result, the proposed formulation passes the patch test for linear electrostatic field as going to be shown in the first numerical example.…”
Section: Variational Formulation and Discrete Governing Equationmentioning
confidence: 82%
See 4 more Smart Citations
“…Because the isoparametric mapping defined in Equation (2) reproduces constant and bilinear fields, it can be shown that the proposed element‐wise nodal integration scheme theoretically preserves the element area . As a result, the proposed formulation passes the patch test for linear electrostatic field as going to be shown in the first numerical example.…”
Section: Variational Formulation and Discrete Governing Equationmentioning
confidence: 82%
“…Assume a convex hull C ( P ) of a node set P=ξitrueQ¯e,i=1,,5frakturR2 defined by [] CPi=15αiξiξiP,αifrakturR+0,i=15αi=1,the parametric convex meshfree method is to construct convex approximations of a given function u in the form uhbold-italicξ=i=15normalΨibold-italicξuiξtrueQ¯ewith the generating function normalΨi:CPR satisfying the following polynomial reproduction property i=15normalΨiξξi=ξξCP.…”
Section: Review On Meshfree‐enriched Finite Element Methodsmentioning
confidence: 99%
See 3 more Smart Citations